2019
DOI: 10.1177/1076029619881409
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylactic Efficacy and Safety of Anticoagulants After Arthroscopic Knee Surgery: A Systematic Review and Meta-Analysis

Abstract: To examine the efficacy and safety of anticoagulants after knee arthroscopy (KA), PubMed, EMBASE, databases of Cochrane Central Register of Controlled Trials, and Chinese National Knowledge Infrastructure were searched up to August 2019 for randomized controlled trials (RCT). Seven RCTs including 4097 patients were demonstrated eligible according to the inclusion and exclusion criteria. The efficacy and safety of thromboprophylaxis were assessed and expressed using relative risk (RR) and 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…Overall, there is a paucity of research on the optimal VTE prophylaxis regime for patients undergoing non-weight-bearing KA procedures, and thus the current recommendations are based on expert consensus on general KA literature. Due to the significantly increased incidence of DVT in non-weight-bearing patients (3.0% vs. 0.7%), the NNT and NNH can be assumed to be much smaller for non-weight-bearing patients relative to data on overall KA (NNT = 26, NNH = 869) 64 . Until further evidence is available, clinicians should consider utilizing LMWH, rivaroxaban or ASA after non-weight-bearing KA procedures such as autologous chondrocyte implantation (ACI), OATS, microfracture, or meniscal repair in order to limit the thrombotic risk associated with prolonged non-weight-bearing.…”
Section: - What Is the Most Optimal Vte Prophylaxis For Patients Unde...mentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, there is a paucity of research on the optimal VTE prophylaxis regime for patients undergoing non-weight-bearing KA procedures, and thus the current recommendations are based on expert consensus on general KA literature. Due to the significantly increased incidence of DVT in non-weight-bearing patients (3.0% vs. 0.7%), the NNT and NNH can be assumed to be much smaller for non-weight-bearing patients relative to data on overall KA (NNT = 26, NNH = 869) 64 . Until further evidence is available, clinicians should consider utilizing LMWH, rivaroxaban or ASA after non-weight-bearing KA procedures such as autologous chondrocyte implantation (ACI), OATS, microfracture, or meniscal repair in order to limit the thrombotic risk associated with prolonged non-weight-bearing.…”
Section: - What Is the Most Optimal Vte Prophylaxis For Patients Unde...mentioning
confidence: 99%
“…In evaluating the efficacy and safety of anticoagulants after KA, Yu et al 41 , performed another systematic review and meta-analysis, which included 4,097 patients. They concluded that anticoagulants could effectively reduce the overall risk of VTE after KA, although the increased risk of bleeding should be considered.…”
Section: - Is Routine Vte Prophylaxis Required For Patients Undergoin...mentioning
confidence: 99%
See 2 more Smart Citations
“…12 Cost-effectiveness has been called into question within the ongoing debate regarding the utility of VTE chemoprophylaxis after knee arthroscopy. 26 Knowledge remains extremely limited on the cost-effectiveness of aspirin or LMWH chemoprophylaxis after knee arthroscopy. Therefore, this study aimed to examine the cost-effectiveness of using aspirin and LMWH to prevent VTE after knee arthroscopy.…”
mentioning
confidence: 99%